1994
DOI: 10.1152/ajpheart.1994.267.5.h1726
|View full text |Cite
|
Sign up to set email alerts
|

Regional electromechanical alternans in anesthetized pig hearts: modulation by mechanoelectric feedback

Abstract: Electrical and mechanical alternans have often been found to coexist. However, the factors controlling their interdependence are not known. In this study we measure regional electrical and mechanical activity during mechanical alternans to investigate this relationship. Mechanical alternans was induced by rapid atrial pacing in 18 anesthetized, open-chest pigs. Regional segmental contraction and monophasic action potential were measured in three areas of left ventricle using epicardial tripodal strain gauges a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…It appears that the electrical phenomenon is the consequence rather than the cause of the contractile alternans, based on several observations that suppression of the contractile alternans also suppressed the electrical alternans (reviewed in 1 ). This could be due to a direct mechanoelectrical feedback 7 on the other hand, shows that at a given level of SR Ca 2ϩ , this relation becomes suddenly very steep. It is the steepness of this relation that underlies the alternans behavior and the depletion/repletion cycle of the SR.…”
Section: Clinical Relevance Of T-wave Alternans and Link To Cellular mentioning
confidence: 96%
“…It appears that the electrical phenomenon is the consequence rather than the cause of the contractile alternans, based on several observations that suppression of the contractile alternans also suppressed the electrical alternans (reviewed in 1 ). This could be due to a direct mechanoelectrical feedback 7 on the other hand, shows that at a given level of SR Ca 2ϩ , this relation becomes suddenly very steep. It is the steepness of this relation that underlies the alternans behavior and the depletion/repletion cycle of the SR.…”
Section: Clinical Relevance Of T-wave Alternans and Link To Cellular mentioning
confidence: 96%
“…For example, Lee et al (1988) have shown electrical-mechanical discordance (short APD associated with large calcium transient) in ischemic hearts. Murphy et al (1994) have also shown electrical-mechanical discordant alternans, but in normal Landrace pigs that were paced rapidly.…”
Section: Voltage and Calcium Couplingmentioning
confidence: 97%
“…Since electrical and mechanical alternans are frequently observed concurrently at the cellular and whole heart level, (Lu et al, 1968;Murphy et al, 1994;Pruvot et al, 2004) it is likely that calcium, an important regulator of cellular contraction and electrophysiology, is involved. Shown in Figure 3 is a simplified diagram of cellular calcium regulation.…”
Section: Intracellular Calcium Regulationmentioning
confidence: 99%
“…For example, measurements were made in a nonworking heart, whereas mechanical loading can potentially influence electrical alternans via mechanoelectrical feedback mechanisms. 7,9,10,17 Also, some evidence suggests that T-wave alternans is dependent on sympathetic stimulation, 5 which is absent in isolated heart preparations. However, sympathetic stimulation does not appear to influence the amplitude of T-wave alternans in patients with structural heart disease and ventricular arrhythmias.…”
Section: Experimental Model Of Steady-state T-wave Alternansmentioning
confidence: 99%
“…The second hypothesis states that T-wave alternans is caused primarily by alternations in repolarization of the action potential, which may give rise to secondary propagation alternans. 11,12,[15][16][17][18] However, the regional membrane changes that underlie the development of T-wave alternans in the intact heart and the possible role such changes play in the mechanism of ventricular arrhythmias are poorly understood because (1) conventional recording techniques cannot be used to monitor cellular membrane potential with sufficient spatial resolution during the development of ECG T-wave alternans and (2) experimental studies have focused on transient alternans during an abrupt change in cycle length (CL) 9,19,20 or alternans during myocardial ischemia, 8,10 -12,21 whereas the majority of patients at risk for sudden cardiac death exhibit T-wave alternans at a relatively constant heart rate (HR) and in the absence of acute ischemia. 13 Therefore, we used the technique of high-resolution optical action potential mapping in an intact heart model of pacing-induced T-wave alternans to determine if T-wave alternans is causally linked to the mechanism of reentry.…”
mentioning
confidence: 99%